Kader Tanggap Stroke: Edukasi Berbasis Teknologi sebagai Strategi Deteksi Dini dan Manajemen Risiko - TRIWIJAYANTI, RENNY (IKesT Muhammadiyah Palembang, 2025)
Abstract Stroke remains a leading cause of disability and death in Indonesia, particularly due to delays in treatment at the community level. This community service program aims to enhance the capacity of health cadres in the early detection of stroke symptoms through training based on the FAST method (Face, Arm, Speech, Time) and the utilization of digital technology. The activity was conducted at Nagaswidak Community Health Center (Puskesmas) in June 2025, involving interactive training, audiovisual education, and the use of a stroke detection application. The results of the pre- and post-tests showed a significant increase in participants' knowledge, from 40% to 90%. In addition, the development of educational media such as leaflets and videos proved effective in improving understanding. The innovative use of technology further strengthened the role of health cadres in delivering information and monitoring high-risk individuals. This program demonstrates that an educational approach combining simple methods and technology can be an effective solution to increase public awareness and quick response to stroke events. Keywords: Stroke, Health Cadres, FAST Technology